Antimotility Effect of Machiluss odoratissima & Sonchus wightianus from Nepal - Subedi*, Amit; Khakural, Dipak; Amatya, Sadhana; Shrestha, Tirtha Maiya; Amatya, Mohan Prasad (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The extracts of Machiluss odoratissima & Sonchus wightianus were subjected to investigate phytochemical, cytotoxic and antimotility properties. The phytochemical screening showed the presence of different compounds. The cytotoxic screening showed that both the extracts are nontoxic. The in vivo study showed the presence of potent antimotility compounds in both plants. Keywords: Machiluss odoratissima, Sonchus wightianus, antimotility, Nepal Email: amitsubedi@gmail.com